Basic Programming Training in Python for Junior High School Students at Al Fitrah Islamic Boarding School - Sudradjat Supian; Mohammad Fadhli Ahmad; subiyanto subiyanto (Research Collaboration Community (RCC), 2023)
This research discusses the implementation of basic programming training using the Python programming language for junior high school (SMP) students at Al Fitrah Islamic Boarding School. The aim of this study is to provide an overview of the training experience and its impact on students' understanding of programming and their proficiency in using Python. The research method used is qualitative with a case study approach. The participants of the study consist of students from the seventh and eighth grades at Al Fitrah Islamic Boarding School. Data was collected through observations, interviews, and tests of students' learning outcomes. The results of the research show that the basic programming training with Python effectively improves students' understanding of programming concepts and develops their computational skills. Additionally, the students demonstrate high interest and enthusiasm in programming activities, indicating strong potential for developing technological skills in the future. This research concludes that basic programming training with Python can be well integrated into the junior high school curriculum to enhance digital literacy and prepare students to face the challenges of an increasingly advanced technological world.